Authentic assessment: Evaluation and its application in science learning - Hanifah, Maria; Irambona, Alfred (Psychology, Evaluation, and Technology in Educational Research, 2019)
The research aims to reveal: (1) the suitability of the implementation of science authentic assessment in Kulonprogo Regency, and (2) the forms of science authentic assessment applied. The study was used the CIPP Stufflebeam evaluation model. The quantitative data were analyzed with T-score, while the qualitative data were analyzed by using Miles & Hubermen. The results of this research are as follows. (1) The implementation of science authentic assessment is wholly fairly effective be seen from T-score analysis 52.44 from the score extent 20-80. (2) The forms of science authentic assessment are practice, portfolio, teacher transcript journal, and daily test, whereas project activity, self assessment, and peer assessment are not done for the heat matter and its movement with T-score 45.14 wholly fairly effective from the score extent 20-80.